The Influence of Work Shifts, Workload, and Work Stress on the Performance of Nurses in Inpatient Ward I at Dr. Saiful Anwar General Hospital, Malang City - Titin Susanti; Miriam Baersady; Joko Prasetyo; Ratna Wardani (STRADA : Jurnal Ilmiah Kesehatan, 2024)
The aim of this study is to determine how the performance of nurses in the inpatient ward I at RSUD Dr. Saiful Anwar Malang is influenced by work shifts, workloads, and work stress. This study uses a quantitative design with a cross-sectional approach. The population of this study is 242 nurses, with a sample of 151 nurses selected using Probability Sampling techniques. The data analysis method used is SPSS with Multiple Linear Regression tests. This study found that among the morning, afternoon, and night shifts, the morning shift has the greatest influence, with a t-value of 2.164 > t-table 1.655 and a significance level of 0.032 < 0.05, indicating that the morning shift positively affects nurse performance. The influence of workload is indicated by a t-value of 9.855 > t-table 1.655 with a significance level of 0.000 < 0.05, meaning that workload negatively affects nurse performance.